The Global Expansion Strategies of Chinese IT Companies: The Case of Lenovo - Liu, Ronghui (2005)
This study explores Chinese IT firms' internationalisation processes and strategies based on a case study of Lenovo internationalisation process and recent acquisition of IBM PCD.